2020
DOI: 10.31219/osf.io/4nvf3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Daily Stress Reactivity: The Unique Roles of Personality and Social Support

Abstract: The specific processes through which social support exerts its influence in daily life are not well understood. Its salutary effects as an environmental variable might be construed as effects of individual differences and related, contextualized personality processes. We investigated the unique effects of personality and social support on daily stress experiences across two 2-day periods (N=391). In line with our preregistered hypotheses, both personality and social support affected the probability of reportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In support of this potential mechanism, a large body of work has shown that these traits do indeed relate to stronger negative affect responses to stressors (Bolger et al, 1989;Bolger & Zuckerman, 1995;Howland et al, 2017;Longua et al, 2009;Mroczek & Almeida, 2004;Myin-Germeys et al, 2009;Parrish et al, 2011;Pearson et al, 2017;Zatura et al, 2005; but not always, see e.g., Hisler et al, 2020).Very few studies have examined whether other Big Five traits relate to negative affect responses to stress, and among those that have, the findings are less consistent. Different studies have shown that conscientiousness, extraversion, agreeableness, and openness amplify (Suls et al, 1998;Wrzus et al, 2021), dampen (Leger et al, 2016), or are unrelated (Kaurin et al, 2021;Leger et al, 2016) to negative affective responses to daily stress. Studies that have examined positive affect responses to daily stress suggest extraversion and neuroticism are unrelated to the strength of positive affect responses (Hisler et al, 2020;Kaurin et al, 2020) and agreeableness buffers against declines in positive affect on stressful days (Leger et al, 2016).…”
Section: Individual Differences In Daily Stress Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this potential mechanism, a large body of work has shown that these traits do indeed relate to stronger negative affect responses to stressors (Bolger et al, 1989;Bolger & Zuckerman, 1995;Howland et al, 2017;Longua et al, 2009;Mroczek & Almeida, 2004;Myin-Germeys et al, 2009;Parrish et al, 2011;Pearson et al, 2017;Zatura et al, 2005; but not always, see e.g., Hisler et al, 2020).Very few studies have examined whether other Big Five traits relate to negative affect responses to stress, and among those that have, the findings are less consistent. Different studies have shown that conscientiousness, extraversion, agreeableness, and openness amplify (Suls et al, 1998;Wrzus et al, 2021), dampen (Leger et al, 2016), or are unrelated (Kaurin et al, 2021;Leger et al, 2016) to negative affective responses to daily stress. Studies that have examined positive affect responses to daily stress suggest extraversion and neuroticism are unrelated to the strength of positive affect responses (Hisler et al, 2020;Kaurin et al, 2020) and agreeableness buffers against declines in positive affect on stressful days (Leger et al, 2016).…”
Section: Individual Differences In Daily Stress Processesmentioning
confidence: 99%
“…Ambulatory assessment research provides evidence for some of these processes in everyday life. The vast majority of this work has focused on links between daily stressors and negative affect, which has consistently shown that people experience more negative emotion on days stressful events occur (Bolger et al, 1989;DeLongis et al, 1988;Diehl & Hay, 2013;Howland et al, 2017;Kaurin et al, 2021;Kiang & Buchanan, 2014;Leger et al, 2016;Mroczek & Almeida, 2004) and less positive affect (Blaxton & Bergeman, 2017;Dunkley et al, 2017;Leger et al, 2016;Nezlek & Allen, 2006;van Eck et al, 1998;Zatura et al, 2005) on days stressful events occur. A few studies have shown daily stress relates to engagement in specific coping strategies (e.g., problem-solving;DeLongis & Holtzman, 2005;Dunkley et al, 2017), health-related behaviors (e.g., alcohol use; Fleming et al, 2021), or specific symptoms (e.g., binge-eating; Goldschmidt et al, 2014), but overall, there is far less ambulatory research on the non-affective components of typical, day-to-day stress responses (i.e., thoughts, behaviors) despite their prominent theoretical role in the cumulative effects of stress.…”
mentioning
confidence: 99%